Introduction - V. I. Yakunin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
This issue of the «Outlines of Global Transformations» taps on the problem of interaction between the state and big transnational businesses in presentday global economy.